SIFAT FISIK, KIMIA DAN ORGANOLEPTIK DODOL HASIL VARIASI RASIO TOMAT DAN TEPUNG RUMPUT LAUT - Maharani Sandiana Lukito; Giyarto Giyarto; Jayus Jayus (JURNAL AGROTEKNOLOGI, 2017)
The process of making a healty meal that does not contain endangering ingredients is truly needed to keep the complete nutritional intake of people who generally consume the meals. Tomato has complete contents including likopen contents, so that product coloring is not needed for certain food products. Dodol commonly made with the raw ingredients sticy rice flour, sugar, and coconut milk which has chewy texture if added and has a high nutrients. The type od seaweed used by this product is Eucheuma cottoni that can result carrageenan which can increase the plasticity and the sturdy texture of dodol. The research aimed to know the effect of ratio tomato and seaweed dodol formulation and also to know the best dodol formulation using seaweed and tomato based on the result of sensory and phisiochemical quality. This study was used a completely randomized design with one single factor that is the comparation of tomato and seaweed composition. This analysis showed that the of with ratio of tomato and seaweed flour significantly affected the brightness (L), a*, b*, the chemical includes water content, dust content, protein content, fiber content, and carbohydrat content dodol. However, it has no really influential of the fat contents. The good treatment and favorites of dodol was combination of 80% tomato and 20% seaweed flour. The best dodol has lightness (L) = 51,83, value of a*= 6,79, value of b*= 6,67, texture 597,70 g/5 mm, water contents about 23 %, dust content about 1,69%, fat contents about6,13 %, protein contents about 11,17 %, rugged fiber content about 1,95 %, and carbohydrat content about 57,74 %. The average of a preference colour, aroma, texture, flavor, and the overall favorite successive result hardness 3,27 ; 3,73 ; 3,60 ; 3,23; 3,77 (preferences value medium up to high). Keywords: dodol, tomato, seaweed flour